Biomechanics of ankle instability. Part 1: Reaction time to simulated ankle sprain - Mitchell, A.; Dyson, R.; Hale, T.; Abraham, C. (Medicine & Science in Sports & Exercise, 2008)
Abstract: Purpose: To test the hypothesis that ankles with functional instability will demonstrate slower muscular reaction times than their contralateral stable ankle (SA) and stable healthy controls to a simulated nonpathological ankle sprain mechanism.